The greenery an urban hydroponic farm and wellness center - Silang, Luiz Marko P.; Sih, Raymond Andrew (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The greenery is a response to the problems brought about by urbanization : food insecurity and unhealthy lifestyle. With the rapid rate of growing population and land use conversion, food security is threatened. There is no facility that focuses on crop production in Metro Manila as the current state of urban agriculture in the country is still limited and underdeveloped. A solution would be an urban hydroponic farm - a controlled environment farm that cultures plants in water, eliminating the need for soil while using the least amount of land possible. The growing trend of healthy living and organic lifestyle choices is a response to the unhealthy and hectic lifestyles of city dwellers. They are more prone to stress, anxiety and poor diet. The creation of a wellness component in the project will offer relaxation, fitness, and self-pampering services within the urban setting. With this, the study fuses urban agriculture and urban retreat - providing a facility that will help food security as well as promote urban well-being through the establishment of an urban hydroponic farm and wellness center. The facility will include spa, fitness gym, crop production areas, research area, restaurant, cafe, commercial area, and a supermarket for the sale of the harvested crops.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Hydroponics -- Metro Manila